PHYSICO- CHEMICAL STANDARDIZATION OF TRADITIONAL MEDICINE”, MUKTA BHASMA IN NANOPARTICLES - Wavare, R. C.; Kadam, V. V.; Sheth, S. M.; Sawant, R. S. (Asian Journal of Pharmaceutical Research and Development, 2014)
Mukta or Pearl, a valuable gem is included in Ratna varga in most of the Ayurvedic texts. As far as the Ayurvedic Pharmaceutical Science is concerned, selection of raw material is the nucleus of the present study which is important step in standardization. Pearl is available in natural and cultured form. However the scarcity and price has limited the use of natural Pearl in medicine. Thus cultured Pearl was used for the study after thorough analysis using ancient as well as modern techniques like Microscopic study. Pearl was subjected to simple and special purification by Swedan in freshly prepared juice of lemon (Citrus acida Linn) and leaves of Jayanti (Sesbania sesban (Jacq.) W. Wight) respectively. Rose water was prepared by a classical method of distillation so as to preserve its essential volatile oils. Mukta Bhasma (MB) was prepared by triturating purified Pearl with Rose water. It was then subjected to heat in 3 laghu puta (puta system of heating) and for firing in each puta, approximately 1.5kg cow dung cakes were used. To assure the quality of MB, Rasa-shastra quality control tests like Nishchandratva, Rekhapurnatva and Varitaratva were used. After MB was found to be in compliance with these tests, it was further analyzed using X-ray diffraction (XRD) analysis. Analysis of raw Pearl and MB revealed that raw Pearl contain CaCO3 in Aragonite form and CaCO3 in Calcite form respectively. Determination of particle size was done by Dynamic light scattering (DLS) and Nanoparticle tracking analysis (NTA) for raw Pearl and MB respectively. The particle size was reduced greatly from114.019 µm to 156 nm. It may be concluded that closed oxidation of Pearl at the temperature up to 700 °C resulted in transformation of Aragonite form into Calcite form. Also thorough trituration, levigation and heat treatment can reduce particle size up to nanometers. Thus it can validate the sukshmata of Bhasma and can be correlated with concept of nanomedicine, essential for its quick and cellular activity.